Paris : Sèvres, Versailles, Saint-Germain, Saint-Denis, Chantilly, Vincennes, Fontainebleau. - Leca, Ph.; Huisman, G.; Monmarché, Marcel (Paris : Hachette, 1924)
Bibliotheek E. Anseele
Frans
Monografie